Causal Factors of Regional Tourism Behavior in Generation Y Tourists - Phansaita, Nalinee; Pattrawiwat, Kanchana; Suveatwatanakul, Chokechai (Journal of Behavioral Science for Development, 2022)
The purposes of this causal research were to validate the causal factors of regional tourism behavior (RTB) and to study the influences of internal and external factors on RTB. The sampling consisted of 534 generation Y tourists in Thailand. Data were collected through questionnaire. Reliability (.79 – .96) and Confirmatory factor analysis and construct reliability (.82 - .98) were performed to evaluate the quality of data. Data was analyzed using the structural equation modeling technique. The results showed that the proposed model fitted with the empirical data (Chi-square = 728.77, df = 166, p < .001, RMSEA = .080, SRMR = .075, GFI = .885, AGFI = .840, NFI = .928, CFI = .945, Chi-square/df = 4.390). The most prominent factors influencing RTB of generation Y tourists were motivation of regional tourism, destination attributes, and reference group. These findings are beneficial to the Tourism Authority of Thailand and those involved in tourism industry such as travel agents, entrepreneurs, and other related service providers. Based on the findings, these organizations in tourism industry can develop the service and product planning to fit with generation Y’s needs in order to promote their RTB.